The Pathology of Weaving and Production of the Hand-woven Carpets: Heriz Region Case Study - Mahjoubi, Sepideh Taravati (Journal of History Culture and Art Research, 2017)
The carpet, as one of the most precious achievement of people, is a culture. The world’s recognition of Iranian carpet and its glorification originates from endeavor of people who have integrated artistic verve with mysterious attractions of national culture and arts. This study is descriptive-analytic. The data were collected through field research method and direct communication with people and workshops of drawing, weaving, and dyeing. In fact, the assessment tools were taken to the field, and data collection was completed by questioning, interview, observation, and shooting. Then, they were used for derivation, classification, and analysis. SPSS software also used to analyze collected data. . According to the result of this study, regarding the latest forecasts for Iranian hand-woven carpet industry, carpet exports will increase in the future. Therefore, it is better to consider the weaving and marketing of the carpet as a luxury product in order to achieve the profits maintaining the incentive of production in all units involved in the hand-woven carpet’s production and also to reduce poor quality carpets available in the market.